Corrosion Durability and Structural Response of Functionally-Graded Concrete Beams - Maalej, M.; Ahmed, Shaikh; Paramasivan, P. (Japan Concrete Institute, 2003)
This paper reports the results of an experimental program on the effectiveness of a Ductile Fiber Reinforced Cementitious Composite (DFRCC) material, which exhibit strain-hardening and multiple-cracking bahavior under flexural loadings, in retarding the corrosion of steel in Reinforced Concrete (RC) beams. Based on the collective findings from theoretically-estimated steel losses, rapid chloride permeability tests, pH value tests, as well as structural tests, it was concluded that Functionally-Graded Concrete (FGC) beams, where a layer of DFRCC material was used around the main longitudinal reinforcement, had a noticeably higher resistance against reinforcement corrosion compared to a conventional RC beam. The better performance of the FGC beams was also evident from the absence of any corrosion-induced cracking and the very low tendency of the concrete cover to delaminate as measured by a concrete-embeddable fiber optic sensor.